I win, you win : the essential guide to principled negotiation - Lyons, Carl (A & C Black, 2007)
This text presents an exploration of how (or if) business and ethics can sit together comfortably, and of the benefits of a principled business approach. It is an aid to getting what you want without compromising your professional integrity.